Does Market Orientation Drive Organisational Social Innovation as A Rescuer for Economic Growth? The Mediating Role of Knowledge Creation - Nur Diyana Mustapha; Suleiman Ibrahim Shelash Mohammad; Asokan Vasudevan; Nur Ilyana Ismarau Tajuddin; Nurul Farhanah Mohd Nasir; Nurulafiza Ramli (Creative Publishing House, 2026)
Tier 2 (Indexed by WOS/Scopus/ERA)